Leaf domatia in montane forest and Caatinga in the semiarid of Pernambuco State: Morphology and ecological implications - Taciana Keila dos Anjos Ramalho; Cláudia Helena Cysneiros Matos; André Laurênio de Melo; Carlos Romero Ferreira de Oliveira; Tatiane Gomes Calaça Menezes; Juliana Kelly de Lima Silva (Acta Scientiarum. Biological Sciences, 2014)
Leaf domatia are cavity-shaped structures of different types or tufts of hairs located at the junction between ribs on the abaxial surface of the leaf blades of various families of angiosperms, serving as protection against phytophagous organisms by harboring beneficial mites, suggesting a mutualistic relationship. There is shortage of inventories of species with such structures; thus the present study examined native woody plant in two habitats of the backwoods of Pernambuco to identify the types of leaf domatia. 86 species were observed,43 inCaatinga area, out of which five had domatia, and43 inthe montane forest, 11 species with domatia. Four types of domatia were observed: hairtufts, pocket, pit and revolute margin. There was predominance of plant species with leaf domatia in the area Carro Quebrado in Triunfo,PernambucoState. These results corroborate the information available in the literature in which domatia are prevalent in more humid environments, and that these structures as micro-habitats influence the maintenance of diverse organisms.